Association of retinal vessel attenuation with visual function in eyes with retinitis pigmentosa - Nakagawa S; Oishi A; Ogino K; Makiyama Y; Kurimoto M; Yoshimura N (Clinical Ophthalmology, 2014)
Satoko Nakagawa, Akio Oishi, Ken Ogino, Yukiko Makiyama, Masafumi Kurimoto, Nagahisa Yoshimura Department of Ophthalmology and Visual Sciences, Kyoto University Graduate School of Medicine, Kyoto, Japan Purpose: To investigate the association between visual changes and retinal vessel attenuation in patients with retinitis pigmentosa (RP).Design: A retrospective, longitudinal, observational cohort study.Methods: We analyzed 45 eyes from 45 subjects who were followed-up for ≥3 years at our clinic. Using the computer-based Interactive Vessel Analysis program, central retinal artery equivalent (CRAE) and central retinal vein equivalent (CRVE) were determined. Age- and sex-matched controls from normal subjects were selected from our archived fundus photograph library. Visual acuity, visual field area (Goldmann perimetry, V4e white test light), mean deviation (Humphrey perimetry, central 10-2 program), and central macular thickness (optical coherence tomography) were analyzed for correlations with CRAE and CRVE.Results: Both CRAE and CRVE were significantly decreased in RP eyes (94.9±13.5 µm and 155.6±20.0 µm, respectively) compared with control eyes (138.1±14.7 µm and 215.0±20.4 µm, respectively, both P<0.001). After 3 years of follow-up, visual field area was associated with both CRAE (r=0.584, P<0.01) and CRVE (r=0.500, P=0.008). A significant association was also observed between mean deviation and CRAE (r=0.298, P=0.047). In eyes with RP, a narrower vessel caliber at baseline was associated with a larger decline in visual acuity over the 3-year follow-up interval (CRAE: r=-0.344, P=0.021; CRVE: r=-0.314, P=0.035).Conclusion: Retinal vessel caliber is associated with some visual functions in patients with RP. Keywords: retinitis pigmentosa, retinal vascular caliber, central retinal artery equivalent, central retinal vein equivalent